Association between mitochondrial DNA content and opium exposure. Issue 10 (6th July 2020) - Ebrahimi, Elmira; Akhavan, Mohammad H.; Akrami, Rahim; Mahmoodi, Majid; Hesami, Sara; Hashemi, Mehrdad; Razavi, Seyed M.; Hadji, Maryam; Zendehdel, Kazem
Abstract: To date, not much study has been done to investigate the mitochondrial DNA (mtDNA) copy number as the potential biomarker for opium exposure. Here, we conducted a cross‐sectional study to determine the relative mtDNA content as the potential biomarker for opium exposure. Quantitative real‐time PCR was performed to investigate the mtDNA copy number variation across 205 individuals, including blood samples of 45 opium users, 41 cigarette users, 47 dual users, and 72 never users of any product. We found a significantly higher mtDNA content among the opium‐only users (adjusted OR: 3.21; 95% CI: [1.34, 7.66]; P = .009) and dual users (adjusted OR: 2.64; 95% CI: [1.15, 6.1]; P = .02) compared to that in never users even after adjustment for confounding factors, age, and sex. Discordantly, analysis of mitochondrial DNA in cigarette smokers revealed an indirect association between cigarette smoking and mtDNA content although it was not statistically significant. The reason behind the increased mitochondrial DNA is unclear. The possible hypothesis is that there might be a way to compensate for the oxidative damage induced by opium consumption. Taken together, our findings indicated that the mtDNA copy number may alter during opium exposure. Since changes in the mitochondrial DNA copy number was associated with the etiology of many diseases including cancer, further investigations on the mtDNA copy number may shed light on the carcinogenicity of opium consumption and means for early detection among the populations who have been exposed to opium and its products.